Astilbic acid induced COLO 205 cell apoptosis by regulating Bcl-2 and Bax expression and activating caspase-3 - ZHENG Xiao-liang; SUN Hong-xiang; LIU Xue-li; CHEN Yun-xiang; QIAN Bo-chu (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect of astilbic acid (3beta, 6beta-dihydroxyolean-12-en-27-oic acid, AA) on human colorectal carcinoma COLO 205 cell proliferation and apoptosis. METHODS: Proliferation of COLO 205 cells was measured by MTT assay. Content of DNA in COLO 205 cell was measured by modified diphenylamine assay. AA-induced morphological changes was observed with fluorescence microscope and transmission electron microscope. DNA fragmentation was visualized by agarose gel electrophoresis. Apoptosis rate and cell cycle distribution were determined by flow cytometric analysis. Expressions of Bcl-2 and Bax proteins were visioned by immunohistochemical analysis. The change of relative mitochondrial transmembrane potential (MTP) in COLO 205 cell was analyzed with FCM after rhodamine 123 staining. RESULTS: The IC50 (96 h) of AA for inhibiting COLO 205 cell proliferation was 61.56+/-0.34 micromol/L. AA induced a marked concentration- and time-dependent inhibition of COLO 205 cell proliferation and reduced the DNA content in COLO 205 cell. Cells treated with AA 64 micromol/L showed typical morphological changes of apoptosis and DNA ladder pattern. The cell cycle was arrested in G0/G1 phase, and the apoptosis rate was 28.25 % for COLO 205 cells treated with AA 64 micromol/L for 48 h. Meanwhile the expression of Bcl-2 protein was decreased while that of Bax was increased and relative MTP was decreased as well. DEVD-CHO 1 micromol/L could increase the viability of COLO 205 cells treated with AA for 48 h. CONCLUSION: AA showed potent inhibitory activity on COLO 205 cells proliferation, and could induce COLO 205 cells apoptosis through disturbing DNA replication, down-regulating Bcl-2 expression, and up-regulating Bax expression, lowering relative MTP, and activating caspase-3 pathway.